UPAYA MENINGKATKAN HASIL BELAJAR SISWA MELALUI PENDEKATAN PENDIDIKAN MATEMATIKA REALISTIK INDONESIA DI SEKOLAH DASAR - Simanjuntak, Haholongan (Universitas Asahan, 2024)
This research aims to improve student learning outcomes through the Indonesian Realistic Mathematics Education (PMRI) approach in Class V of SD Negeri 106162 Medan Estate. The research method used is classroom action research involving teachers and students in a process of reflection and improvement. Data collection was carried out through observation, tests and interviews. PMRI steps are applied in planning, implementation, observation and reflection. The research results show a significant increase in student learning outcomes after implementing PMRI. PMRI-based mathematics learning encourages students to be more active, creative and independent in understanding mathematical concepts. This is proven by the increase in student observation results, namely the score obtained was 72.20 (fair) in the first observation activity (cycle I) which increased to 85 (good) in the second observation activity (cycle II). Apart from that, increasing student learning outcomes can achieve success, as evidenced by the first observation (cycle I) and second observation (cycle II), namely from 65.50% (fairly good) to 87.50% (very good).